The Use of Guidedâ€“Questions Combined with Buzz Group Technique to Increase Studentsâ€™ Writing Skill of SMP Muhammadiyah Pagaralam - M. Bambang Purwanto; Ariya Agustin (Universitas PGRI Palembang, 2021)
Buzz Group Tehcnique Â are a technique in teaching which divide students into a group activity in which groups of students have a brief discussion (for example, five minutes) to generate ideas or answer specific questions. Â Buzz group can be used in many different ways and are most often used in combination with other techniquesâ€. In this research the writer will combined two kinds of technique, Guided-question Combined with Buzz Group Technique. Guided-question Combined with Buzz Group Technique means combine two kinds of technique in teaching learning process those are Guided-question with Buzz Group Technique to enhance both techniques. The research design used in this study was one-group pre test-post test design. The study employed both quantitative and qualitative data analyses fromÂ pre-and post-tests, a questionnaire, and an interview. The participants of theÂ study wereÂ 35Â first-yearÂ studentsÂ enrollingÂ inÂ aÂ compulsory readingÂ courseÂ called Communication and Reading Skills at Darussalam Polytechnic of Palembang.Â It is shown shown by a significant difference in quality of studentsâ€™ in-class written experimental designs between the treatment and control groups (19.943 versus 17.943; p>0.0489). However, draft (22.337 versus 18.929; p>0.0760) and paper grades (27.186 versus 27.971; p>0.6726) did not vary significantly whether or not students were provided with the guided questions. There were several intervening and potentially confounding factors, due to the nature of the paper writing process in our labs, which included peer review of paper drafts that were not limited to students within the treatment and control groups.. The results suggested that 1) The English writing ability post test mean score of students was higher than the pre test mean score at the 0.05 level of significance; 2) most students were satisfied with their own writing ability; 3) they enjoyed working inÂ group andÂ agreed thatÂ mindÂ mapping technique wasÂ aÂ useful technique and can be applied to non- English subjects. Findings and implications for further research are discussion.Â